ANALISIS KESALAHAN PENGGUNAAN TANDA BACA DALAM SKRIPSI MAHASISWA PRODI PENDIDIKAN BAHASA DAN SASTRA INDONESIA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS NIAS RAYA - Maria Karlina Pramita Harita (Universitas Nias Raya, 2026)
The problem in the research is that there are several errors in the use of punctuation marks in several student theses. This research approach is qualitative with a descriptive type. The results of this research show that: 1) There were 33 (thirty three) errors in using full stops. 2) There were 10 (ten) errors in using commas. 3) There were 4 (four) errors in the use of question marks. 4) There were 8 (eight) errors in using colons. The conclusions in this research are 1) The spelling errors that are most often found in student theses are full stops, commas, question marks and colons. 2) Of the four types of punctuation, the most common errors are in the use of dots. 3) The fewest punctuation errors are question marks. The suggestions in this research are 1) For educators to continue teaching the correct use of punctuation to students. 2) For students, especially those at Nias Raya University, to continue learning regarding the correct use of punctuation according to the applicable spelling. 3) To other researchers to carry out further research related to errors in the use of punctuation marks both on the same research object and on other objects.